The benefits and risks of menopause hormone therapy for the cardiovascular system in postmenopausal women: a systematic review and meta-analysis - Yimeng Gu; Fangfang Han; Mei Xue; Miyuan Wang; Yuxiao Huang (BMC, 2024)
Abstract Background Menopause hormone therapy (MHT), as an effective method to alleviate the menopause-related symptoms of women, its benefits, risks, and potential influencing factors for the cardiovascular system of postmenopausal women are not very clear. Objectives To evaluate cardiovascular benefits and risks of MHT in postmenopausal women, and analyze the underlying factors that affect both. Search strategy The EMBASE, MEDLINE, and CENTRAL databases were searched from 1975 to July 2022. Selection criteria Randomized Clinical Trials (RCTs) that met pre-specified inclusion criteria were included. Data collection and analysis Two reviewers extracted data independently. A meta-analysis of random effects was used to analyze data. Main results This systematic review identified 33 RCTs using MHT involving 44,639 postmenopausal women with a mean age of 60.3 (range 48 to 72 years). There was no significant difference between MHT and placebo (or no treatment) in all-cause death (RR = 0.96, 95%CI 0.85 to 1.09, I2 = 14%) and cardiovascular events (RR = 0.97, 95%CI 0.82 to 1.14, I2 = 38%) in the overall population of postmenopausal women. However, MHT would increase the risk of stroke (RR = 1.23, 95%CI 1.08 to 1.41,I2 = 0%) and venous thromboembolism (RR = 1.86, 95%CI 1.39 to 2.50, I2 = 24%). Compared with placebo, MHT could improve flow-mediated arterial dilation (FMD) (SMD = 1.46, 95%CI 0.86 to 2.07, I2 = 90%), but it did not improve nitroglycerin-mediated arterial dilation (NMD) (SMD = 0.27, 95%CI − 0.08 to 0.62, I2 = 76%). Compared with women started MHT more than 10 years after menopause, women started MHT within 10 years after menopause had lower frequency of all-cause death (P = 0.02) and cardiovascular events (P = 0.002), and more significant improvement in FMD (P = 0.0003). Compared to mono-estrogen therapy, the combination therapy of estrogen and progesterone would not alter the outcomes of endpoint event. (all-cause death P = 0.52, cardiovascular events P = 0.90, stroke P = 0.85, venous thromboembolism P = 0.33, FMD P = 0.46, NMD P = 0.27). Conclusions MHT improves flow-mediated arterial dilation (FMD) but fails to lower the risk of all-cause death and cardiovascular events, and increases the risk of stroke and venous thrombosis in postmenopausal women. Early acceptance of MHT not only reduces the risk of all-cause death and cardiovascular events but also further improves FMD, although the risk of stroke and venous thrombosis is not reduced. There is no difference in the outcome of cardiovascular system endpoints between mono-estrogen therapy and combination therapy of estrogen and progesterone.